Cremation Practices and the Creation of Monument Complexes: The Neolithic Cremation Cemetery at Forteviot, Strathearn, Perth & Kinross, Scotland, and its comparanda. (4th October 2017) - Noble, Gordon; Brophy, Kenneth; Hamilton, Derek; Leach, Stephany; Sheridan, Alison
Abstract : Around the beginning of the 3rd millennium calbc a cremation cemetery was established at Forteviot, central Scotland. This place went on to become one of the largest monument complexes identified in Mainland Scotland, with the construction of a palisaded enclosure, timber structures, and a series of henge monuments and other enclosures. The cemetery was established between 3080 and 2900 calbc, probably in the 30th century calbc, which is contemporary with the cremation cemetery at Stonehenge. Nine discrete deposits of cremated bone, representing the remains of at least 18 people, were identified. In most instances they were placed within cut features and, in one case, a series of cremation deposits was associated with a broken standing stone. This paper includes the first detailed assessment of the cremated remains at Forteviot and the features associated with the cemetery, and explores how the establishment of this cemetery may have been both a catalyst and inspiration for the elaborate monument building and prolonged acts of remembrance that occurred at this location over a period of almost 1000 years. The paper also outlines the parallels for Forteviot across Britain and, for the first time, draws together the dating evidence (including Bayesian modelling) for this major category of evidence for considering the nature of late 4th/early 3rd millennium calbc society. The results and discussion have wide implications and resonances for contemplating the establishment and evolution of monument complexes in prehistoric Britain and beyond. RÉSUMÉ: Pratiques d'incinération et la création des complexes monumentaux: Le cimetière à incinération néolothique de Forteviot, Strathearn, Perth et Kinross, Ecosse et ses comparables de Gordon Noble et Kenneth Brophy Aux alentours du début du 3ème millénaire av.J.-C cal un cimetière à incinération fut établi à Forteviot, centre de l'Ecosse, RU. Ce lieu devait devenir l'un des plus grands complexes monumentaux jamais identifiés en Ecosse continentale, avec la construction d'un enclos à palissade, de structures en bois de construction et d'une série de monuments à talus et fossé et autres enceintes. Le cimetière fut établi entre 3080 av. J.-C. et 2900 av.J.-C.cal, probablement au 30ème siècle av.J.-C. cal, ce qui est contemporain du cimetière à incinération de Stonehenge. Neuf dépôts diffus d'os calcinés, représentant les restes d'au moins 18 personnes, furent identifiés. Dans la plupart des cas, ils se trouvaient à l'intérieur de structures creusées et, dans un des cas, une série de dépôts d'incinérations étaient associée à une pierre dressée cassée. Cet article inclut la première évaluation détaillée des restes incinérés de Forteviot et des indices associés au cimetière et explore comment l' établissement de ce cimetière a pu être à la fois un catalyste et une inspiration pour la construction de ce monument élaboré et les actes prolongés de mémoire qui s'y déroulèrent sur une période de presque 1000 ans. L'article décrit aussi les parallèles de Forteviot à travers la Grande-Bretagne et rassemble, pour la première fois, les témoignages de datations (y compris la modélisation bayésienne) de cette catégorie majeure de témoignages pour l'étude de la nature de la société de la fin du 4ème/début du 3ème millénaire av. J, -C. cal. Les résultats et la discussion ont de vastes implications et résonances pour la reflexion sur l'établissement et l'évolution des complexes monumentaux dans la Grande-Bretagne préhistorique et au-delà. ZUSAMMENFASSUNG: Praktiken der Leichenverbrennung und die Schaffung monumentaler Komplexe: Der neolithische Brandbestattungsplatz von Forteviot, Strathearn, Perth und Kinross, Schottland, und seine Komparanda, von Gordon Noble und Kenneth Brophy Am Beginn des 3. Jahrtausends calbc wurde ein Brandbestattungsplatz in Forteviot in Zentralschottland, Großbritannien, angelegt. Dieser Platz entwickelte sich zu einem der größten Komplexe mit Bestattungsmonumenten, den wir auf dem schottischen Festland kennen, mit der Konstruktion eines Erdwerkes mit Palisade, Holzstrukturen und einer Reihe von Henge-Monumenten und anderen Grabenwerken. Der Bestattungsplatz wurde zwischen 3080 und 2900 calbc eingerichtet, wahrscheinlich im 30. Jahrhundert calbc, was zeitgleich mit dem Brandbestattungsplatz von Stonehenge ist. Neun separate Deponierungen verbrannter Knochen wurden identifiziert, die die Überreste von mindestens 18 Personen repräsentieren. In den meisten Fällen fanden sie sich innerhalb eingetiefter Befunde, in einem Fall war auch eine Reihe von Deponierungen von Leichenbrand mit einem zerbrochenen Menhir assoziiert. Dieser Beitrag umfasst auch die erste detaillierte Auswertung der Leichenbrände von Forteviot sowie der mit dem Brandbestattungsplatz assoziierten Befunde und untersucht, wie die Einrichtung dieses Bestattungsplatzes sowohl ein Katalysator als auch eine Inspiration für das Errichten elaborierter Monumente und für fortgesetzte Akte des Gedenkens gewesen sein kann, die an diesem Platz über einen Zeitraum von fast 1000 Jahren stattfanden. Zudem zeigt der Beitrag die Parallelen für Forteviot in Großbritannien auf und bringt erstmals die Datierungen (einschließlich Bayesscher Modellierung) für diese zentrale Kategorie archäologischer Daten zur Erörterung des Charakters der Gesellschaft des späten 4./ frühen 3. Jahrtausendsbc zusammen. Die Resultate und Diskussionen haben weitreichende Bedeutung für Überlegungen zur Entstehung und Entwicklung von Komplexen von Monumenten im prähistorischen Großbritannien und darüber hinaus. RESUMEN: Prácticas de cremación y la creación de complejos monumentales: el cementerio de cremación de Forteviot, Strathearn, Perth y Kinross, y sus comparaciones, por Gordon Noble y Kenneth Brophy Aproximadamente a principios del III milenio calbc se estableció un cementerio de cremación en Forteviot, Escocia central, Reino Unido. Este emplazamiento llegó a ser uno de los complejos monumentales más grandes identificados en el interior de Escocia, con la construcción de un recinto empalizado, estructuras de madera y una serie de recintos y henge. El cementerio se estableció entre el 3080 y el 2900 calbc, probablemente en el III milenio calbc, por lo que es contemporáneo al cementerio de cremación de Stonehenge. Se han identificado nueve depósitos individualizados de hueso quemado, que representan los restos de, al menos, 18 personas. En la mayoría de los casos, se localizaron dentro de estructuras recortadas y, en un caso, una serie de depósitos de cremación estaba asociada a un hito de piedra quebrado. Este artículo incluye la primera evaluación detallada de los restos cremados de Forteviot y de las características relacionadas con el cementerio, y analiza cómo el establecimiento de este cementerio pudo haber sido un catalizador y una inspiración para la compleja construcción monumental y para los prolongados actos de conmemoración que ocurrieron en este lugar durante un periodo de al menos 1000 años. El artículo también señala los paralelos de Forteviot a lo largo de Gran Bretaña y, por primera vez, aúna la evidencia cronológica (incluyendo la modelización bayesiana) para este importante tipo de evidencia en el seno de la sociedad de finales del IV e inicios del III milenio cal BC. Los resultados y la discusión tienen una amplia implicación y relevancia para reflexionar sobre el establecimiento y la evolución de los complejos monumentales en la Prehistoria de Gran Bretaña y de fuera de ella.